Usable Space Versus Food Quantity in Bobwhite Habitat Management - Douglas S. Cram; Ronald E. Masters; Fred S. Guthery; David M. Engle; Warren G. Montague (National Quail Symposium Proceedings, 2017)
We studied the response of northern bobwhite (Colinus virginianus) foods (plants and invertebrates), usable space, and populations following thinning and burning on the 60,000-ha pine (Pinus spp.)-grassland restoration area in the Ouachita National Forest, Arkansas, to examine 2 hypotheses commonly used to manage bobwhite habitat: 1) usable space (suitable permanent cover) and 2) food quantity (an element of habitat quality). We estimated invertebrate food abundance using sweep nets and abundance of food-producing plants using herbaceous and woody stem counts. The disk of vulnerability was used to index usable space. We used whistling-male counts to index population response. Relative abundance, mass, and frequency of occurrence of invertebrate foods and richness, density, and frequency of occurrence of bobwhite food-producing plants increased following thinning and fire. Relative abundance of whistling males was greatest in thinned stands 3 growing seasons post-burn and in thinned but unburned stands. We found food supply was related to usable space following treatment. However, food abundance alone did not explain bobwhite population response, whereas, usable space was predictive for bobwhite response. By comparing treated stands with similar usable space but different food quantity, we observed no differences in bobwhite abundance. Neural models suggested bobwhite population response was less sensitive to changes in food supply relative to changes in usable space. We recommend that managers should seek first to provide usable space (suitable permanent cover in low basal area stands), recognizing that adequate food supply will likely be a side effect of management to this end.
Keywords: Arkansas; Colinus virginianus; food quantity; management philosophies; northern bobwhite; Ouachita Highlands; pine-grassland restoration; prescribed fire; usable space